AN ANALYSIS ON INTRINSIC ELEMENTS OF KUNGFU PANDA 3 MOVIE - Susanto (Journey: Journal of English Language and Pedagogy, 2019)
The objectives of the research are, first to analyze kinds the intrinsic elements find on Kungfu Panda 3 movie. And second, to find out the moral values on Kungfu Panda 3 movie. The data were collected from the dialogues, performance and attitude by the characters on Kungfu Panda 3 movie. The result of this research shown there were six kinds of intrinsic elements on Kungfu Panda 3 movie. Namely character and characterization, theme, point of view, plot, setting, and moral value. The result of this research also shown that there were two kinds of moral values, namely values of being and values of giving.